Identifying and Explaining the Reconstruction of Business Models Mix with Corporate Entrepreneurship Approach in Tourism Industry - Amir Mohammad Colabi; Simin Karimirad (Muṭāli̒āt-i Mudīriyyat-i Gardishgarī, 2020)
Today, the best method to be dynamic to confront the environmental changes, which lead to a deep gap between country’s needs and operation of corporations, is reconstructing the business models. Regarding the importance of reconstruction of business models, acquiring the advantage of competitiveness, the goal of this investigation is identifying the reconstruction of business models mix. The investigation approach is qualitative and developmental in terms of purpose. The statistical sample includes 13 directors who have had the experience of entrepreneurship within the tourism industry. The tool to collect data is interview; to analyze such data, method of content analysis has been selected. What is presented as the result of the investigation is that four main factors of reconstruction corporation’s business models mix with concentration on processes, the major structure and based on profit models, within the framework of 4Cs are corporate culture, corporate social responsibility, creating shared values and capabilities.